2005
DOI: 10.1111/j.1651-2227.2005.tb01915.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival after surgery for congenital heart defects: Does reduced early mortality predict improved long‐term survival?

Abstract: Early mortality has been substantially reduced in congenital heart defect patients, and corresponds with significantly improved long-term survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 18 publications
1
28
0
5
Order By: Relevance
“…Over the past decades, advances in diagnostic and surgical techniques and medical treatment of congenital heart disease (ConHD) have gradually evolved and have significantly improved long-term survival of patients with ConHD [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, advances in diagnostic and surgical techniques and medical treatment of congenital heart disease (ConHD) have gradually evolved and have significantly improved long-term survival of patients with ConHD [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Advances in the medical and surgical treatment of patients with congenital heart disease (CHD) have resulted in improved survival, and more children survive to adulthood [1]. Recently, the number of adolescents and adults with CHD has increased rapidly, and in the nearer future, it will exceed that in the children group [2].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to a report from our hospital on a subcohort of 970 children operated on for CHD between 1990 and 1999, 7 3 other studies specifically targeting survival after CHD surgery have been published during the past decade, all based on retrospective data. Nieminen et al 5 reported that, among patients <15 years of age who underwent surgery in 1953 to 1989 (75% in 1970-1989), 15-year survival in patients with UVH, TGA, and TOF was 45%, 65%, and 82%, respectively.…”
Section: Survivalmentioning
confidence: 99%